KEMAMPUAN GOOD CORPORATE GOVERNANCE DAN CSR MEMODERASI PENGARUH LIKUIDITAS, SOLVABILITAS, DAN PROFITABILITAS PADA NILAI PERUSAHAAN - Mariani, Wayan Eny; Rasmini, Ni Ketut; Harta Mimba, Ni Putu Sri (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.05.NO.09.TAHUN 2016, 2016)
This study aims to determine the capability of good corporate governance and corporate social responsibility to moderate the relationship between liquidity, solvability, profitability, and the company’s value. This study use three theory such as, agency theory, signaling theory, and contingency theory. The sampling method of this study is purposive sampling therefore the number of sample are 17 firms. Independent variable in this study are current ratio, debt to equity ratio, and return on asset. The dependent variable in this study is company’s value and good corporate governance and corporate social responsibility as moderating variables. The result of this study showed that good corporate governance and corporate social responsibility have no capability to moderate the relationship between liquidity, solvability, profitability, and value firm. Future studies may use another method to measure the of good corporate governance and corporate social responsibility
Keywords: Current Ratio, Debt To Equity Ratio, Return On Asset, Good Corporate Governance, Corporate Social Responsibility